Implementation of aid as pharmaceutical innovation towards national and foreign pharmaceutical practice - L. M. Unhurian; O. I. Bielyaieva; I. B. Pietkova (Kazimierz Wielki University, 2017)
Over the past four decades there was a tendency to shift the focus of pharmaceutical activities, primarily focused on providing medicines to help patients. So the role of the pharmacist has evolved, and he turned from the person who manufactures and sells drugs into a provider of services and information. The most important thing is that the pharmacist gives aid to the patient, taking him under his professional care. Moreover, the task of a pharmacist is to ensure that the aid received by the patient, is administered correctly, the most effective among all available options, the most safe and right for this patient. The practice of pharmaceutical care is new and significantly different from what was the activity of pharmacists in last years. As pharmacists often were unable to bear the responsibility for pharmacotherapy, having neither appropriate documentary justification nor possibilities for monitoring, control and analysis of treatment. Taking over this responsibility is the cornerstone in the practice of pharmaceutical care.